Staphylococcus spp. in the oral cavity and periodontal pockets of chronic periodontitis patients - Loberto, JCS; Martins, CAD; Santos, SSF dos; Cortelli, JR; Jorge, AOC (Soc Brasileira Microbiologia, 2004)
Staphylococcus spp are not usually isolated from the oral cavity, and when this occurs, they are considered to belong to the transitory microbiota. Individuals with periodontal disease represent possible reservoirs of these opportunistic bacteria in the oral cavity. The use of antibiotics for treatment of periodontal disease or other infections may predispose to the increase of the number of Staphylococcus spp. in the oral cavity. These microorganisms easily become resistant to antibiotics, and may result in superinfection. The purpose of this study was to evaluate the presence of Staphylococcus spp. in the oral cavity and in periodontal pockets of patients with chronic periodontitis, identify the isolates and verify the relationship between the presence of Staphylococcus spp. in the oral cavity and presence of periodontal pockets. The study included eighty-eight patients, 25-60 years of age, with chronic periodontitis, and at least two sites with probing depth >= 5mm. Individual data examination was assessed. Then, samples were colleted from the periodontal pocket with the aid of paper tips and from the oral cavity through mouth rinses. Out of the total of patients, 37.50% presented Staphylococcus spp. in the periodontal pocket and 61.36% in the oral cavity, 27.27% presented the bacteria in both sites. S. epidermidis was the most prevalent specie in the periodontal pocket (15.9%) and oral cavity (27.27%). The occurrence of higher proportions of nonresident's microorganisms in subgingival samples and oral sites may represent significant problem in causing and maintaining periodontal infections.
Keywords: Staphylococcus; opportunistic bacteria; periodontitis